The Growth of Jabon (Anthocephalus cadamba Roxb. Miq.) in Less Optimum Environment and Its Respons to Fertilizer Application - Irdika Mansur; Surahman Surahman (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2011)
Jabon (Anthocephalus cadamba Roxb. Miq.) is one kind of industrial tree that grows fast (fast growing species), as a producers of wood to meet the demands of Indonesian timber which continues to increase. In the 70's 100% wood industry in Indonesia only rely on natural forests as a source of supply. The rate of degradation natural forests continues to increase causing sharply reduced timber supply. Jabon is one kind of superior wood that can be developed through Industrial Plantation Forest and the Community Forest. However, the silviculture information in its development is still limited, especially the profit of advanced fertilization and selection area. The aim of this study was to determine the growth of jabon in less optimum environment (poor drainage and under shade conditions), to determine the influence of fertilizer application on the growth of jabon and to get the optimum dose of fertilizer application.